Detection, transmission, pathogenicity and chemical treatment of fungi in Ceiba speciosa seeds - Lazarotto,Marília (2010)
The aim of this work was to evaluate fungus association, transmission and pathogenicity, besides chemical seed treatment in Ceiba speciosa seeds from different regions of southern Brazil. Seven seed samples were used to do the germination test, fungus detection by blotter test and potato-dextrose-agar (PDA), fungus transmission and pathogenicity tests; besides, chemical seed treatments were tested. Germination ranged from 0 to 59,5%. The following fungi were associated in the seeds: Fusarium sp., Alternaria sp., Colletotrichum sp., Curvularia sp. and Pestalotia sp.; in addition, Fusarium sp. was found in all the samples. Alternaria sp. and Fusarium sp. were transmitted by seeds. The isolates of Alternaria sp., Colletotrichum sp. and Fusarium sp., were pathogenic to seedlings and seeds. The seed treatment with methyl tiophanate and the combination captan + methyl tiophanate reduced Fusarium sp. incidence.